Credit between cultures : farmers, financiers, and misunderstanding in Africa - Shipton, Parker MacDonald (Yale agrarian studies., 2010)
Parker Shipton offers a range of perspectives on the process of lending & borrowing in Africa. His conclusions challenge the conventional wisdom of the past half century about the need for credit among African farmers.